Pendampingan Belajar dalam Kefasihan Membaca Al-Qur’an melalui Bimbingan Les Mengaji Maghrib bagi Anak-Anak Usia Sekolah Dasar di Desa Karang Tengah Serdang Bedagai - Nurdiana Siregar; Lailatun Nur Kamalia Siregar; Intan Nuraini; Khoirul Bariah Rambe; Laila Qadaria; Wapiatul Khairiah (Prodi Perpustakaan dan Sains Informasi, 2023)
In this community service, there is a problem in reading the Qur'an, namely the lack of understanding of tajweed and not being able to distinguish makhorijul letters in elementary school-age children in Karang Tengah Village, Serdang Bedagai. The solution offered by the community service team is to provide assistance for children who have difficulty reading the Qur'an. The purpose of mentoring is so that elementary school children are fluent in reading the Qur'an. In Islam, learning the Qur'an is an obligation that must be carried out and developed for every individual Muslim, because it will be directly related to worship such as prayer, hajj and prayer. The method of implementing the mentoring is by using the tutoring method which is carried out regularly at the end of the maghrib prayer. Mentoring is carried out by 4 mentors as many as 4 elementary school-age children. In the mentoring activities, the experience gained by these children is getting tajweed material, hearing the correct pronunciation of the hijaiyah letters, practicing applying tajweed and makhorijul letters when reading the Qur'an and answering questions from the mentor related to the material that has been taught. The recitation tutoring activities at maghrib time have succeeded in making the children of Karang Tengah Village, Serdang Bedagai, 85% more fluent in reading the Qur'an.